Dancing with Python Learn Python Software Development from Scratch and Get Started with Quantum Computing. - Sutor, Robert S. (Packt Publishing, Limited, 2021)
Millions of software developers use Python, and it is a powerful foundation for classical and quantum computing. Dancing with Python teaches you how to create elegant and efficient code using Pythonic techniques. Its integrated introduction to quantum computing development helps you extend your skills to the next major computing technology.